L'acculturation aux littéracies universitaires : exemple de l'apprentissage et enseignement de l'emploi de "on" à l'aide du logiciel AntConc - Anne Prunet (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
The use of the personal pronoun "on" in French academic literacies is particularly important. We will show how the acquisition of "on" is made possible by the use of the AntConc software. Our approach is based on French for academic purposes and literacies; in that frame the notion of discourse genre is relevant.